Ideologías y actitudes lingüísticas en el Chile del siglo XIX: los reparos de Andrés Bello a las Correcciones lexigráficas de Valentín Gormaz - Rojas, Darío (2015)
Within the studies of objections and comments to dictionaries of provincialisms, this paper analyzes, within a cognitive approach, the linguistic attitudes and ideologies that Andrés Bello show in his commentary to the Correcciones lexigráficas, posthumously published. Bello’s objections to Gormaz exemplify the despair the author felt about the idiomatic poverty among Chilenian writers.